PERTAHANAN NEGARA DAN GENDER WANITA DI MASA PANDEMI COVID19 DI INDONESIA - Christine S.T. Kansil; Michelle Prawira; H K Martono (PROSIDING SERINA, 2021)
This article discusses the Covid-19 pandemic, defense and gender. This relates to the role of a woman as a housewife, as well as the mother of the nation. The research method used is library research with a descriptive analysis system to find solutions to the problems raised. The aim is to find out the impact of the Covid-19 pandemic situation on the role of women in national defense. It is known that housewives have the obligation to help their children study online, support the family economy, social welfare, take care of their husbands, grandfathers and/or grandmothers when experiencing independent isolation at home, and make their families happy. While women as mothers of the nation are related to state defense, security, safety, economy, social welfare, and others. However, with the presence of the Covid-19 pandemic, women's duties as housewives and mothers of the nation are now starting to be disrupted and ultimately result in reduced and not optimal women's empowerment. Therefore, the government must increase the defense of gender